2018
DOI: 10.3389/fphys.2018.00670
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of GABAergic and Adrenergic Neurotransmissions on Paraventricular Nucleus of Hypothalamus in the Control of Cardiac Function

Abstract: Sympathetic premotor neurons of the paraventricular hypothalamus (PVN) play a role in hemodynamics adjustments during changes in body fluid homeostasis. However, PVN contribution to the tonic control of cardiac function remains to be systematically studied. In this study, we assessed whether GABAergic and adrenergic synapses, known for being active in the PVN, are involved in the control of cardiac function. Adult male Wistar rats (250–350 g; n = 27) were anesthetized with urethane (1.2–1.4 g/kg i.p.) and unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…However, other studies found that microinjections of the ␤-adrenergic receptor agonist isoprenaline in WKY and SD rats had no effect on blood pressure (48, 82) but did increase baroreflex sensitivity in SD rats (82). On the other hand, PVN injections of the ␣ 1 -adrenergic receptor agonist phenylephrine or the nonselective ␣-adrenergic receptor antagonist phentolamine significantly increased renal sympathetic nerve activity and heart rate without an effect on blood pressure (10,48). Our experiments demonstrated that, in control GFP animals, selective catecholaminergic lesioning in the NTS induced a marked increase in blood pressure, whereas stimulation of ␤-adrenergic receptors in the PVN resulted in significant hypotensive responses.…”
Section: Discussionmentioning
confidence: 97%
“…However, other studies found that microinjections of the ␤-adrenergic receptor agonist isoprenaline in WKY and SD rats had no effect on blood pressure (48, 82) but did increase baroreflex sensitivity in SD rats (82). On the other hand, PVN injections of the ␣ 1 -adrenergic receptor agonist phenylephrine or the nonselective ␣-adrenergic receptor antagonist phentolamine significantly increased renal sympathetic nerve activity and heart rate without an effect on blood pressure (10,48). Our experiments demonstrated that, in control GFP animals, selective catecholaminergic lesioning in the NTS induced a marked increase in blood pressure, whereas stimulation of ␤-adrenergic receptors in the PVN resulted in significant hypotensive responses.…”
Section: Discussionmentioning
confidence: 97%
“…Increased activity at excitatory (eg, glutamatergic and cholinergic ) synapses has been linked to cardiovascular injury [48][49][50][51][52]. Similarly, serotonergic and GABAergic synapses in the CNS in uence cardiovascular activity [53][54][55]while central cholinergic transmission induces cardiovascular changes in hypertensive rats [56]. Our results demonstrate that the aberrant activity of hippocampal neurons induced by AMI can be at least partly mitigated by EA.Our data showed that the expression of multiple genes was altered by AMI and restored by EA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, CRS not only triggered changes in the heart and peripheral nervous system; it also resulted in remodeling of central sites. The PVN is one of the most important brain centers that regulate sympathetic tone (45), stress response (46, 47), and cardiac function (48). The PVN and hypothalamus of CRS mice exhibited down‐regulated expression of TH as well as adrenergic signaling‐related genes.…”
Section: Discussionmentioning
confidence: 99%